Proceedings of Abu Dhabi International Petroleum Exhibition and Conference 2006
DOI: 10.2523/101401-ms
|View full text |Cite
|
Sign up to set email alerts
|

Techniques Used To Monitor and Remove Strontium Sulfate Scale in UZ Producing Wells

Abstract: Scale deposition in completion strings is becoming a threatening problem to produce and safely operate wells completed in the Upper ZAKUM (UZ) oil field. Calcite or Calcium Carbonate (CaCO3) scale mostly found in the upper part of the production string, and Celestite or Strontium Sulphate (SrSO4) mostly found in the lower part of the production string, are the common type of scales encountered in Upper ZAKUM producing wells. Injection seawater (rich in Sulphate) and formation water (rich in Strontium ions) mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A drastic decrease in productivity from 30,000 Barrels of Oil Per Day (bopd) to zero within 24 h was observed in the North Sea Miller field [38]. The Alba field located on the UK continental shelf and the Zakum field located in Abu-Dhabi, are included among the world's largest oil fields where sulphate and carbonate scale were found [39,40]. More information about the composition and characterization of waxy crude oils in different regions is shown in Table 2.…”
Section: Nitrogen Compoundsmentioning
confidence: 99%
“…A drastic decrease in productivity from 30,000 Barrels of Oil Per Day (bopd) to zero within 24 h was observed in the North Sea Miller field [38]. The Alba field located on the UK continental shelf and the Zakum field located in Abu-Dhabi, are included among the world's largest oil fields where sulphate and carbonate scale were found [39,40]. More information about the composition and characterization of waxy crude oils in different regions is shown in Table 2.…”
Section: Nitrogen Compoundsmentioning
confidence: 99%
“…It is well known in the oil industry that strontium ions cause large amounts of scaling on the inner surface of the pipelines leading to a drastic reduction in oil production and huge financial losses [ 17 , 18 , 19 , 20 ]. One of the major challenges of the oil industry is to prevent scale development in the oil production pipelines [ 20 , 21 , 22 , 23 , 24 , 25 ]. This scaling is due to the mixing of injected seawater with the produced water from the well.…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent fieldwork [ 21 ] in Upper Zakum (4th largest oil field in the world) in Abu Dhabi, it was reported that the main scales present in the oil wells in this field are calcium carbonate (CaCO 3 ) in the upper part of the wells and strontium sulfate (SrSO 4 ) in the lower part of the wells. From the field data and records, the report clearly emphasized the big challenge faced in removing the strontium sulfate scale due to its hardness.…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple studies and research conducted on scale monitoring, testing, and optimization of scale inhibitors [1][2][3]. The current industry practice for managing scale programs relies on the determination of scale inhibitor concentration in the scaling brine and then relates this concentration to program performance.…”
Section: Introductionmentioning
confidence: 99%